The Relationship between Childhood Trauma Experiences and Psychotic Vulnerability in Obsessive Compulsive Disorder: An Italian Cross-Sectional Study - Davide Fausto Borrelli; Laura Dell’Uva; Andrea Provettini; Luca Gambolò; Anna Di Donna; Rebecca Ottoni; Carlo Marchesi; Matteo Tonna (Brain Sciences, 2024)
People with obsessive compulsive disorder (OCD) are at increased risk of developing psychotic disorders; yet little is known about specific clinical features which might hint at this vulnerability. The present study was aimed at elucidating the pathophysiological mechanism linking OCD to psychosis through the investigation of childhood trauma experiences in adolescents and adults with OCD. One hundred outpatients, aged between 12 and 65 years old, were administered the Yale–Brown Obsessive Compulsive Scale (Y-BOCS) and its Child version (CY-BOCS), as well as the Childhood Trauma Questionnaire (CTQ); Cognitive–Perceptual basic symptoms (COPER) and high-risk criterion Cognitive Disturbances (COGDIS) were assessed in the study sample. Greater childhood trauma experiences were found to predict psychotic vulnerability (p = 0.018), as well as more severe OCD symptoms (p = 0.010) and an earlier age of OCD onset (p = 0.050). Participants with psychotic vulnerability reported higher scores on childhood trauma experiences (p = 0.02), specifically in the emotional neglect domain (p = 0.01). In turn, emotional neglect and psychotic vulnerability were found higher in the pediatric group than in the adult group (p = 0.01). Our findings suggest that childhood trauma in people with OCD may represent an indicator of psychotic vulnerability, especially in those with an earlier OCD onset. Research on the pathogenic pathways linking trauma, OCD, and psychosis is needed.